On Some Curious Phenomena Observed in Making a Test of a Piece of Bessemer Steel - William Kent (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1880)
ABOUT a year ago, the writer had occasion to assist Mr. John L. Gill, Jr., of the Pittsburgh. Car-wheel Works, in making a trial of his new testing machine. A piece of Bessemer steel, of about .34 carbon, was used as a test-piece, turned to a sectional area of one square inch for a length of five inches between shoulders, and pro¬vided with large round heads, which were fitted to what is called the " Wade grip." Measurements of elongation, accurate to , 1/10000 of an inch, were made by a special apparatus containing two micrometer screws, with electric contact attachment. The machine was operated by hand-power. Readings of elongation were taken at each increment of 2000 pounds stress per square inch, up to 44,000 pounds, the elongation corresponding to the latter figure being .0088 inch. The elongations up to this point remained almost exactly proportional to the stresses, the strain diagram, as shown on the Plate, from the origin to the point A, being a straight line (the deviation of no observation from the straight line being greater than .0002 inch). There being no indication of an approach to the elastic limit, the attendant at the hand-wheel and scale-beam was told to proceed as usual and move the poise forward 2000 pounds, or to 46,000, and turn the wheel until the beam was balanced. Noticing that the beam did not rise in the usual time, and that the elongation was increasing rapidly, the writer called to the attendant to stop turning the hand-wheel and to push the poise backwards until the scale-beam balanced. Instead of balancing at between 44,000 and 46,000 pounds, as was expected, it balanced at 40,000 pounds, and the elongation had increased to .0343 inch (or more than four times that recorded at 44,000 pounds), as plotted at the point B, the dotted line between A and B showing the supposed course of the strain diagram between these two points. Immediately upon recording the elongation the writer said to Mr. Gill, who was standing alongside: "This phenomena is without a parallel in my experience, and I know of but one way to account for it. The piece must actually be broken in its interior, through a flaw or weak portion of the metal. The test-piece is now equivalent to a tube, with